New microRNAs in Drosophila--birth, death and cycles of adaptive evolution. - Yang Lyu; Yang Shen; Heng Li; Yuxin Chen; Li Guo; Yixin Zhao; Eric Hungate; Suhua Shi; Chung-I Wu; Tian Tang (PLoS Genetics, 2014)
The origin and evolution of new microRNAs (miRNAs) is important because they can impact the transcriptome broadly. As miRNAs can potentially emerge constantly and rapidly, their rates of birth and evolution have been extensively debated. However, most new miRNAs identified appear not to be biologically significant. After an extensive search, we identified 12 new miRNAs that emerged de novo in Drosophila melanogaster in the last 4 million years (Myrs) and have been evolving adaptively. Unexpectedly, even though they are adaptively evolving at birth, more than 94% of such new miRNAs disappear over time. They provide selective advantages, but only for a transient evolutionary period. After 30 Myrs, all surviving miRNAs make the transition from the adaptive phase of rapid evolution to the conservative phase of slow evolution, apparently becoming integrated into the transcriptional network. During this transition, the expression shifts from being tissue-specific, predominantly in testes and larval brain/gonads/imaginal discs, to a broader distribution in many other tissues. Interestingly, a measurable fraction (20-30%) of these conservatively evolving miRNAs experience "evolutionary rejuvenation" and begin to evolve rapidly again. These rejuvenated miRNAs then start another cycle of adaptive - conservative evolution. In conclusion, the selective advantages driving evolution of miRNAs are themselves evolving, and sometimes changing direction, which highlights the regulatory roles of miRNAs.